2000
DOI: 10.1136/bmj.320.7248.1502
|View full text |Cite
|
Sign up to set email alerts
|

Relation between troponin T concentration and mortality in patients presenting with an acute stroke: observational study

Abstract: Objective To assess whether a raised serum troponin T concentration would be an independent predictor of death in patients with an acute ischaemic stroke. Design Observational study. Setting Auckland Hospital, Auckland, New Zealand. Subjects All 181 patients with an acute ischaemic stroke admitted over nine months in 1997-8, from a total of 8057 patients admitted to the acute medical service. Main outcome measures Blood samples for measuring troponin T concentration were collected 12-72 hours after admission; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(141 citation statements)
references
References 14 publications
9
125
2
5
Order By: Relevance
“…Cardiac abnormalities, as judged by release of cardiac enzymes, changes in electrocardiography (ECG), or clinical or echocardiographic evidence of left ventricular dysfunction usually develop just after intracerebral disorders (i.e., stroke, subarachnoid hemorrhage) (Bhagat et al 1997;James et al 2000). The exact underlying pathophysiological mechanism of this myocardial dysfunction could not be determined in many cases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac abnormalities, as judged by release of cardiac enzymes, changes in electrocardiography (ECG), or clinical or echocardiographic evidence of left ventricular dysfunction usually develop just after intracerebral disorders (i.e., stroke, subarachnoid hemorrhage) (Bhagat et al 1997;James et al 2000). The exact underlying pathophysiological mechanism of this myocardial dysfunction could not be determined in many cases.…”
Section: Methodsmentioning
confidence: 99%
“…However the studies searching for cTnT which is more sensitive and specific to myocardium after stroke, is relatively scarce (James et al 2000;Parekh et al 2000). Moreover, to our knowledge, its associations with stroke volume and type of stroke have not been investigated thoroughly.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the amount of cTnT elevation is associated with a poor prognosis among patients with cerebrovascular disease. 13,14) However, the present study excluded patients with prior cerebrovascular disease. Reports indicate that DM and LV hypertrophy, which might be associated with ongoing myocardial damage according to the present study, are risk factors for cerebrovascular disease.…”
Section: Pathophysiological Roles Of Ongoing Myocardial Damage For Dementioning
confidence: 99%
“…13,14) The present study evaluated the relationship between elevated cTnT and the development of cardiovascular and cerebrovascular diseases in hypertensive patients without left ventricular (LV) systolic dysfunction.…”
mentioning
confidence: 99%